Popcorn Brain dan Artificial Intelligence Terhadap Kemampuan Belajar Mahasiswa Dengan Motivasi Belajar Sebagai Variabel Intervening - Mahzum, Muhammad; Charli, Chintya Ones (Universitas Labuhanbatu, 2025)
The rapid development of digital technology has had a significant impact on student learning patterns, especially with the emergence of the phenomenon of Popcorn Brain and artificial intelligence (Artificial Intelligence). Popcorn Brain is a condition in which individuals have difficulty concentrating and thinking deeply due to exposure to instant information overload. Meanwhile, the use of AI in education can improve learning efficiency, but also potentially reduce the critical power and analytical ability of students. This study aims to analyze the effect of Popcorn Brain and AI on student learning ability, with learning motivation as an intervening variable. The research method used is quantitative with survey approach. Data were collected through questionnaires based on Likert scale and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results showed that both Popcorn Brain and AI had a significant influence on students ' learning abilities. Learning motivation acts as an intervening variable that reinforces the relationship between AI and learning ability, although Popcorn Brain's influence on learning ability through motivation is relatively smaller. Therefore, more effective learning strategies are needed to reduce the negative impact of instant information consumption in the student learning process.